Comparison of Nitric Oxide Concentration in Seminal Fluid between Infertile Patients with and without Varicocele and Normal Fertile Men - Mehraban, Darab; Ansari, Mohammad; Keyhan, Hossein; Sedighi Gilani, Mohammadali; Naderi, Gholamhossein; Esfehani, Fateme (Urology Journal, 2009)
Introduction: Elevated nitric oxide (NO) levels have been shown to have toxic effects on sperm function and motility. This study was conducted to compare NO levels in the seminal fluid of infertile men with varicocele with those of infertile and fertile men without varicocele. Materials and Methods: Semen samples were obtained from 40 infertile men with varicocele (group 1), 40 infertile men without varicocele (group 2), and 40 fertile volunteers without varicocele (group 3). NO levels in the seminal plasma of patients in each group were measured and compared. In infertile men with varicocele, semen parameters, including sperm count and motility, and grade of varicocele were also determined. Results: Mean NO concentrations were 52.34 ± 26.62 µmol/L, 37.06 ± 20.39 µmol/L, and 33.7 ± 18.99 µmol/L in groups 1, 2, 3, respectively. Concentrations in group 1 were significantly higher than were those in groups 2 and 3 (P = 0.001). In group 1, no significant correlations were seen between NO concentrations and grades of varicocele, sperm count, sperm motility, or ages of the patients. Conclusion: Data from the current study suggest a possible role of NO in damaging the sperm function in varicocele as demonstrated by an increased concentration of NO in the seminal fluid of infertile men with varicocele compared with the seminal fluid of fertile and infertile men without varicocele.